CHARACTERISTICS AND PATTERNS OF PSYCHIATRIC ILLNESS AMONG CHILDREN AND ADOLESCENTS AT A TERTIARY CARE HOSPITAL IN KARACHI PAKISTAN - Suleman, Fawad; Iqbal, Samiya; Sher, Zainab; Halo, Liaquat Ali; Pirani, Shahina (Journal of Pakistan Psychiatric Society, 2024)
ObjectiveTo assess the patterns of psychiatric illness among children and adolescents presented at psychiatric clinic of a public sector teaching hospital in Karachi, Pakistan.Study DesignA cross sectional studyPlace and Duration of the studyThe study was conducted at the Child and Adolescent Psychiatry outpatient clinic of the National Institute of Child Health (NICH) in Karachi, during February 2019 to October 2019.MethodologyUsing consecutive, non-probability sampling, all male and female participants, age less than 18 were recruited from the study setting. Data collection was done using a pre-designed semi-structured proforma. The data was analyzed using descriptive statistics.ResultsA total of 250 pediatric patients visiting the psychiatric clinic were enrolled in this study. These included 161 (64.4%) males and 89 (35.6%) females. Mean age was 9.55 ±3.374 years. 31 (12.4%) patients reported directly to the psychiatry clinic while 160 (64%) patients were referred from pediatric medicine clinics. The remaining 59 (23.6%) patients were referred from adult psychiatry clinics. 126 (50.4%) were diagnosed to have stress and related disorders, 85 (34%) patients were diagnosed with neurodevelopmental disorders. About 5 (2%) patients were diagnosed with psychotic and mood disorders, 34 (13.6%) were diagnosed with other nonspecific disorders.ConclusionThe study reveals a male predominance among children and adolescents at a public sector hospital, with a high referral rate from pediatricians. The diverse mental health issues include stress, neurodevelopmental, and other diagnoses, highlighting the need for deeper investigation and targeted clinical attention.